Depth oriented brief therapy how to be brief when you were trained to be deep - and vice versa - Ecker, Bruce; Hulley, Laurel (Jossey-Bass social and behavioral science series, 1996)
Depth-Oriented Brief Therapy is written for therapists, psychologists, counselors, social workers, psychiatrists, and other helping professionals who want to meet the challenge of managed care without losing the deeper levels of change traditionally associated with long-term or existential work